The effect of promotional mix on repurchase intention of lubricant customer trough attitude - Yulistyan, Andrio Hafidz; Wahyudi, Triyono Arief (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
Customer loyalty is essential in any industry, especially the oil industry. Customer loyalty is influenced by their attitude towards the product or service, which the promotional mix can influence. The promotional mix includes sales promotion, word of mouth, social media, and electronic word of mouth. This research aims to determine how the promotional mix dimensions affect customers' repurchase intention by influencing their attitude. The research sample consisted of 210 respondents who were customers who used oil in the Jabodetabek area—the results of the research hypothesis test support all hypotheses. The strongest factor influencing repurchase intention is social media promotion. The SEM method results for all variables from the promotion mix showed acceptable results, which can be implemented in company management. In conclusion, sales promotion, word of mouth, social media, and electronic word of mouth can influence customer attitudes and create repurchase intention. The limitations of this study are the limited areas of development and the fact that the dimensions analyzed were only attitudes towards promotion mix and repurchase intention